Aerodynamic Fields inside S-Shaped Baffled-Channel Air-Heat Exchangers. (11th May 2021) - Menni, Younes; Lorenzini, Giulio; Kumar, Ravinder; Mosavati, Babak; Nekoonam, Saeed
Abstract : A numerical study of an especial heat exchanger (HE) equipped with complicated geometry baffles was performed in this research study. This shell-and-tube HE could be applied in various engineering applications like solar collectors. It can be acknowledged that generating longitudinal vortices in the flow results in enhancing the turbulent convective heat transfer. In order to generate these vortices, S-shaped baffles can be applied. It should be noted that computational analysis of shell-and-tube HEs is considered a challenging task due to these vortices. So, in this study, a commercial CFD software has been used for solving the problem and important equation and numerical approach used in the simulation have been explained. The aerodynamic aspect with respect to stream function, mean, axial, and transverse velocities, dynamic pressure, turbulent dissipation rate, turbulence kinetic energy, turbulent viscosity, and turbulence intensity fields was included in this research. This study reports many physical phenomena, such as the turbulence, instability, flow separation, and the appearance of reverse secondary currents. The average speed changed in different areas, where it is low next to the baffles. Velocity amounts are paramount around the upper channel's wall, starting from the upper left side of the last baffle to the exit. This increase in velocity can be justified by a reduction in flow area and pressure augmentation.